Payment for ecosystem services markets on Aboriginal land in Cape York Peninsula: Potential and constraints - Michael Winer; Helen Murphy; Harold Ludwick (United Nations Research Institute for Social Development (UNRISD), 2012)
In the global arena, improving environmental outcomes at the same time as ensuring social equity outcomes for disadvantaged landholder groups has become increasingly important. This is especially true in regions with pressing environmental problems populated by low-income indigenous land stewards. The ability of Payment for Ecosystem Services (PES) schemes to lift poor people out of poverty and, in particular, the potential for PES schemes to improve social and welfare conditions in remote Australian indigenous communities is increasingly being recognized. Based on research in Cape York, Australia, this paper argues that a new approach to environmental management is needed to incorporate PES market participation by indigenous landowners. This is because the current framework for environmental management on Cape York is failing on two fronts: it is delivering suboptimal environmental outcomes and constraining the economic development aspirations of traditional owners. Current barriers to participation by indigenous communities in the Cape York Peninsula in PES markets-including legislative constraints and the existence of weak Aboriginal land and property rights-must be overcome. This paper argues that insufficient government funding and lack of indigenous involvement in design and implementation of natural resource management (NRM) has resulted in increased environmental risk in the region and an NRM system characterized by insufficient, unreliable and short-term government funding. Such funding regimes result in communities becoming financially dependent, politically vulnerable and disempowered from decision making, discouraging entrepreneurism and career development opportunities. There has been an overall lack of formal recognition and at times active undermining of Aboriginal governance structures by the government and non-governmental organizations (NGOs) to achieve political outcomes, further weakening Aboriginal negotiation and governance capability and disempowering indigenous NRM on their lands...
Keywords: 330